Robert Irwin Getty garden - Weschler, Lawrence (The J. Paul Getty Museum, 2020)
"This new edition features interviews with Robert Irwin by critic Lawrence Weschler about the creation of the Central Garden at the Getty Center in Los Angeles, along with new photography of the mature garden"--